2014
DOI: 10.1002/aenm.201400678
|View full text |Cite
|
Sign up to set email alerts
|

Towards High‐Performance Nonaqueous Redox Flow Electrolyte Via Ionic Modification of Active Species

Abstract: Nonaqueous redox fl ow batteries are emerging fl ow-based energy storage technologies that have the potential for higher energy densities than their aqueous counterparts because of their wider voltage windows. However, their performance has lagged far behind their inherent capability due to one major limitation of low solubility of the redox species. Here, a molecular structure engineering strategy towards high performance nonaqueous electrolyte is reported with signifi cantly increased solubility. Its perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
228
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 207 publications
(236 citation statements)
references
References 38 publications
8
228
0
Order By: Relevance
“…However, ferrocene's low solubility (e.g., <0.1 M in carbonate-based solvent) restricts its use in RFBs for grid energy storage. Recently, Wei et al described a structural modification strategy to greatly enhance the solubility of ferrocene [79]. Figure 6a shows the structure of the ferrocene derivative (Fc1N112-TFSI).…”
Section: Ferrocene Derivativesmentioning
confidence: 98%
“…However, ferrocene's low solubility (e.g., <0.1 M in carbonate-based solvent) restricts its use in RFBs for grid energy storage. Recently, Wei et al described a structural modification strategy to greatly enhance the solubility of ferrocene [79]. Figure 6a shows the structure of the ferrocene derivative (Fc1N112-TFSI).…”
Section: Ferrocene Derivativesmentioning
confidence: 98%
“…127 Through the density functional theory calculation, they found that the preferential sites for the solvent molecules were near and around the ionic region due to its higher positive charge density around the functionalized ferrocene cation. The ionic pendant intensifies the interactions between the solvent molecules and the functionalized ferrocene, resulting in a greatly enhanced solubility up to 0. .…”
mentioning
confidence: 99%
“…[20][21][22][23][24][25][26] Even fewer studies have incorporated advanced flow cell designs to minimize area specific resistance (ASR) and increase area specific power density.…”
mentioning
confidence: 99%
“…8 To date, most NAqRFB studies have focused on molecular discovery and electrolyte characterization at dilute active species concentrations, [13][14][15][16][17][18][19] with only a few published attempts to engineer higher performance systems with concentrated electrolytes. [20][21][22][23][24][25][26] Even fewer studies have incorporated advanced flow cell designs to minimize area specific resistance (ASR) and increase area specific power density. 21,[27][28][29] At present, reported NAqRFBs exhibit inadequate performance and durability, 8 but identifying performance limiting factors can be difficult because shortcomings could be attributed to active species degradation (e.g., instability, insolubility, chemical incompatibility), insufficient separator selectivity (e.g., crossover, low conductivity), or poor cell design (e.g., slow mass transfer, resistive electrodes, high pressure drop).…”
mentioning
confidence: 99%